Negative differential resistance in the I–V curves of Al2O3/AlGaN/GaN MIS structures. Issue 7 (12th January 2016) - Shen, Lingyan; Cheng, Xinhong; Wang, Zhongjian; Cao, Duo; Li zheng,; Wang, Qian; Zhang, Dongliang; Li, Jingjie; Yu, Yuehui
Abstract : Negative differential resistance is firstly observed in I – V characteristic of GaN MIS structure, which is induced by intervalley electron transfer. Abstract : Negative differential resistance (NDR) induced by inter-valley electron transfer is often observed in Gunn diodes. In this paper, we report the observation of this novel NDR phenomenon in Al2 O3 /AlGaN/GaN metal–insulator–semiconductor (MIS) structures. This study offers new understanding on the gate characteristics of GaN HEMTs. The NDR is found to be more prominent at low temperature. The voltage ( V NDR ) at the onset of the NDR is temperature dependent and decreases with temperature. Measurement results support the possibility that the NDR originates from the inter-valley electron transfer in conjunction with tunneling. The fitting results of the measured I – V with tunneling models reveal that TAT (trap assisted tunneling) is the dominating mechanism at low gate bias and FNT (Fowler–Nordheim tunneling) is dominant at relatively high gate voltage. Moreover, the energy difference between valley Γ and valley M–L in the GaN conduction band can be estimated by the voltage ( V NDR ), which is linearly related to the crystal temperature.